A LOW-COST METHOD FOR THE DETECTION OF DUPLICATE HOLDINGS AMONG GENEBANK ACCESSIONS - F. . Yndgaard; I. G. Loskutov; S. O. Solberg; O. N. Kovaleva; A. . Kolodinska-Brantestam; J. T. Svensson (Труды по прикладной ботанике, генетике и селекции)
A set of 185 pairs of accessions with the same name from the Russian and Nordic collections of barley were grown in the field in Pushkin and were scored by the same person using a set of morphological descriptors. No differences were detected in the majority of the pairs (63%).In four out of six pairs no differences were detected for any of the agro-botanical characters. The accessions are most likely duplicates. In 13% of the pairs, the accessions were probably distinct and another 24% fell in-between these categories and required further investigation. Simple screening can reduce the number of duplicates. [The work is dedicated to Sergey M. Alexanian, Vice Director for Foreign Relations of VIR, who passed away in 2014].